A Review of the Next Day Effects of Alcohol on Subjective Mood Ratings - McKinney, Adele (Current Drug Abuse Reviews, 2010)
Alcohol-induced hangover is commonly experienced after excessive alcohol consumption. This paper presents a critical review of literature on the next day effects of excessive alcohol consumption on subjective ratings of mood. The review has identified 7 comprehensive studies which have followed either the pharmacological approach or the naturalistic approach to investigating the mood state of the individual during the post intoxication hangover phase. There is diversity in the tools used to assess mood and in the aspects of mood measured, this needs to be addressed in future research however there is a general finding that mood is decreased during hangover.
Keywords: Nausea